A patient with combined pituitary hormone deficiency and osteogenesis imperfecta associated with mutations in LHX4 and COL1A2 - Nalinee Hemwong (Journal of Advanced Research, 2020)
Genetic disorders have been shown to co-occur in individual patient. A Thai boy with features of osteogenesis imperfecta (OI) and combined pituitary hormone deficiency (CPHD) was identified. The causative mutations were investigated by whole exome and Sanger sequencing. Pathogenicity and pathomechanism of the variants were studied by luciferase assay. The proband was found to harbor a novel de novo heterozygous missense mutation, c.1531G > T (p.G511C), in COL1A2 leading to OI and a heterozygous missense variant, c.364C > T (p.R122W), in LHX4. The LHX4 p.R122W has never been reported to cause CPHD. The variant was predicted to be deleterious and found in the highly conserved LIM2 domain of LHX4. The luciferase assays revealed that the p.R122W was unable to activate POU1F1, GH1, and TSHB promoters, validating its pathogenic effect in CPHD. Moreover, the variant did not alter the function of wild-type LHX4, indicating its hypomorphic pathomechanism. In conclusion, the novel de novo heterozygous p.G511C mutation in COL1A2 and the heterozygous pathogenic p.R122W mutation in LHX4 were demonstrated in a patient with OI and CPHD. This study proposes that the mutations in two different genes should be sought in the patients with clinical features unable to be explained by a mutation in one gene. Keywords: Thyroxine, Bisphosphonate, Mutation, Insulin, Skeleton, Growth